Komparasi metode activity based costing system dan metode penetapan tarif jasa rawat inap Rumah Sakit Umum PKU Muhammadiyah Jatinom - Nurrokhmini, Alfiati (Nur Science Institute, 2022)
This study aims to get an overview of the effect of hospital operating costs on inpatient service rates at RSU PKU Muhammadiyah Jatinom. The results of this study will provide management with information for making decisions about setting rates for inpatient services at PKU Muhammadiyah Jatinom General Hospital in the future. It used a comparative descriptive analysis that compared the activity-based costing system method and the method of determining inpatient service rates used by the hospital. Based on the research and evaluation of the data obtained, operational costs affect the hospital's determination of the inpatient service rate. Hospitals can lose patients if they continuously use conventional methods without considering their activities' costs. Predictions using the activity-based costing system method are used as a reference to determine the rates of inpatient services that will be achieved in the future and to anticipate future losses.